Pelatihan Pembuatan Pakan Ikan Lele pada Petani di Kelurahan Suka Karya Kota Jambi: Pengabdian - Metha Monica; Hajar Setyaji; Suryaanto; Mukhsin (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
One of the determining factors for the success of catfish cultivation is fish feed. Catfish feed is an intake or food given to catfish which is useful for meeting nutritional needs that are useful for meeting nutritional needs to support the growth, survival and health of catfish. The target audience for community service activities is a group of fish farmers in Sukaa Karya Village, Jambi City. The number of catfish farmers is 10 people. The pattern of implementation of the activity method will be taken in stages, namely a. Preliminary survey and Problem Identification b. Training Activities, c. Skills Activities, d. Evaluation. Based on the results of the community service activities, the following conclusions can be drawn: The response of fish farmers in participating in this community service activity in making catfish feed is very positive and shows a willingness to know and master skills in making catfish feed. Making catfish feed with coconut cake is one alternative for catfish feed.